Time Is of the Essence—Early Activation of the Mevalonate Pathway in Apple Challenged With Gray Mold Correlates With Reduced Susceptibility During Postharvest Storage - Naets, Matthias; Van Hemelrijck, Wendy; Gruyters, Willem; Verboven, Pieter; Nicolaï, Bart; Keulemans, Wannes; De Coninck, Barbara; Geeraerd, Annemie H. (Frontiers in Microbiology, 2022)
Apple is typically stored under low temperature and controlled atmospheric conditions to ensure a year round supply of high quality fruit for the consumer. During storage, losses in quality and quantity occur due to spoilage by postharvest pathogens. One important postharvest pathogen of apple is Botrytis cinerea. The fungus is a broad host necrotroph with a large arsenal of infection strategies able to infect over 1,400 different plant species. We studied the apple-B. cinerea interaction to get a better understanding of the defense response in apple. We conducted an RNAseq experiment in which the transcriptome of inoculated and non-inoculated (control and mock) apples was analyzed at 0, 1, 12, and 28 h post inoculation. Our results show extensive reprogramming of the apple’s transcriptome with about 28.9% of expressed genes exhibiting significant differential regulation in the inoculated samples. We demonstrate the transcriptional activation of pathogen-triggered immunity and a reprogramming of the fruit’s metabolism. We demonstrate a clear transcriptional activation of secondary metabolism and a correlation between the early transcriptional activation of the mevalonate pathway and reduced susceptibility, expressed as a reduction in resulting lesion diameters. This pathway produces the building blocks for terpenoids, a large class of compounds with diverging functions including defense. 1-MCP and hot water dip treatment are used to further evidence the key role of terpenoids in the defense and demonstrate that ethylene modulates this response.